Adverse childhood experiences and social media use in adulthood. Evidence from a novel EU survey - Matija Kovacic; Cristina Elisa Orso (Global Labor Organization (GLO), 2024)
This paper explores whether individuals that grew up in adverse environments are more likely to engage in excessive use of social media later in life. We rely on a novel EU-wide survey that comprises information on social media usage time, patterns, motivations, and potential overuse, together with a rich set of individual-specific socio-economic conditions and childhood experiences. We find that adverse childhood environments, and especially the presence of close relatives with severe drinking and mental health problems, significantly increase the likelihood of social media overuse in adulthood. Moreover, we document interesting differential patterns between types of social media platforms, as well as between active and passive users. Adverse childhood environments have a disproportionate impact on passive overuse of digital social network platforms, resulting in more frequent neglect of work and family responsibilities. Finally, we show that the effect of childhood conditions on some specific aspects of social media use is mediated by loneliness and social connectedness in adulthood. Our findings have significant policy implications because the interplay between the excessive social media use and adverse childhood experiences may jointly undermine individuals' well-being and cognitive development.
Keywords: L82; D91; J12; I12; I31; 330; Adverse childhood conditions; social media overuse; neglect; loneliness; social connectedness